18F-Fluoro-2-deoxyglucose positron emission tomography in the evaluation of gastrointestinal malignancies. (1st June 2003) - Chin, B B; Wahl, R L
Abstract : Positron emission tomography with 18 F-fluoro-2-deoxyglucose is an imaging technology that is demonstrating increasing utility in the evaluation of gastrointestinal malignancies.